Answer: (8^{12})^3=8^{12\times 3}=8^{36}
Step-by-step explanation:
Given : the expression (8^{12})^3
We have to simplify the given expression and choose the correct from the given options.
Consider the expression (8^{12})^3
Using property of exponents,
\left(a^b\right)^c=a^{b\times c}
We have,
(8^{12})^3=8^{12\times 3}=8^{36}
Answer:
y-int. is -4 (red)
Step-by-step explanation:
Answer:
-3
Step-by-step explanation:
H = -3
J = -1
J = -1
M=2
(-3+-1)+(-1+2)=-3
U turn negative numbers from mixed numbers to improper fractions the same way u do with positive...u just temporarily disregard the negative sign.
Example :
- 2 2/3.....temporarily disregard the negative sign......take ur whole number (2) and multiply it by ur denominator (3) giving u 6, then add that to ur numerator (2) giving u 8....then put that number over the original denominator (3) giving u 8/3...and then put back ur negative sign...-8/3